New species and records of ptyctimous mites (Acari, Oribatida) from the Philippines - Niedbała, Wojciech; Ermilov, Sergey G. (Zootaxa, 2017)
A list of identified oribatid ptyctimous mites from the Philippine Islands Luzon, Mindanao, Polillo and Samar Islands, including 16 species, 10 genera and 5 families, is provided. The genus Mesotritia and species Atropacarus (Atropacarus) griseus (Niedbała, 1984), A. (Atropacarus) striculus (C. L. Koch, 1835) and A. (Hoplophorella) stilifer (Hammer, 1961) are recorded for the Philippine fauna for the first time. Two new species, Mesotritia paraflagelliformis Niedbała sp. nov. (Oribotritiidae) and Plonaphacarus leonilae Niedbała sp. nov. (Steganacaridae), are described from leaf litter. The supplementary descriptions of Oribotritia aokii Mahunka, 1987 and Hoplophthiracarus illinoisensis (Ewing, 1909) are presented based on the materials from the Philippines.